Enhancement of Primary Sludge Sedimentation Using Polyelectrolytes - Chałupka, Natalia; Cłapa, Daria; Janiak, Kamil; Muszyński-Huhajło, Mateusz (Instal, 2025)
This article presents the results of research on improving the efficiency of primary sludge sedimentation in gravity thickeners through the use of cationic polyelectrolytes. Many wastewater treatment plants face the challenge of undersized thickeners, which do not provide sufficient phase separation. This results in high solids content in the supernatant stream and and its recirculation to the beginning of the treatment line. This leads to excess loading of primary settling tanks, increases the risk of methanogen development in primary settling tanks and thickeners, and often prevents the accurate determination of raw sewage composition. This study utilizes a methodology for determining the limiting flux, a parameter characterizing the maximum separation capacity of the sedimentation process. The evaluation was conducted on samples of raw sludge and sludge conditioned with polyelectrolytes. The limiting flux for the primary sludge was 62.4 kg DS/m2·d, and for the conditioned sludge, 170.4 kg DS/m2·d. The obtained results showed that the addition of polyelectrolytes significantly increased the limiting flux, confirming improved sedimentation properties and the possibility of more efficient operation of gravity thickeners. The research results can provide a basis for implementing optimized organic coagulant dosing in engineering practice, as well as for the design and modernization of sedimentation facilities.
Keywords: cationic polyelectrolytes; primary sedimentation; wastewater treatment; gravity thickening of primary sludge